Leisure-time activities of public elementary school teachers in the division of Cagayan 1 - Lasam, Estrella (Pattugalan) 1935- (s.n.], 1969)
The main intention of the study is to serve as a pace-setter for other studies about recreation or as a basis for future teachers' recreation program to help improve the leisure-time activities of teachers. The study sought to make a survey of the leisure-time facilities available to public elementary school teachers in Cagayan I and of the leisure-time activities engaged in by them. The significance of the study lies in its possible contributions in the formulation of a list of prescribed leisure-time activities and as a basis for holding future workshops, seminars, and conferences to help improve the recreational activities of teachers in the Division of Cagayan I.